Pengaruh Program Kegiatan Perilaku Hidup Bersih dan Sehat (PHBS) Di Sekolah Terhadap Sikap Kemandirian Anak Usia 4-5 Tahun - Siti Wahidah; Enjang; Nurul Fauziah (CV Putra Publisher, 2024)
This study aims to evaluate the effect of the Clean and Healthy Lifestyle Behavior (PHBS) activity program on the independence attitude of children aged 4-5 years at Pembina State Kindergarten. Using a one-group pretest-posttest design, this study involved 20 children in group A as samples. The research process included a pretest, four sessions of PHBS learning activities, a post-test, and interviews with educators. The results showed that the average pretest score was 59.70, indicating that most children had not shown adequate independence, such as completing tasks independently. After the implementation of the PHBS program, the average post-test score increased significantly to 160.91. Statistical analysis with SPSS produced a t-test value of -29.24, with df = 19 and a significance value (2-tailed) = 0.000, indicating a significant increase in children's independence after the implementation of the PHBS program. This finding is consistent with previous theories and studies stating that the PHBS program can effectively increase children's independence. Thus, it can be concluded that the PHBS program has a significant positive influence on increasing the independence of children aged 4-5 years at Pembina State Kindergarten. This program has proven effective in supporting children's ability to complete daily tasks independently and in managing personal health.